2014
DOI: 10.1089/jayao.2014.0012
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Testis Cancer and Semen Abnormalities Before Orchiectomy: A Systematic Review

Abstract: Purpose: Testicular germ cell tumors (TGCT) are the most common solid organ malignancy in young men. It is a largely curable disease, so the extent to which it affects quality of life-including male fertility-is important. Abnormal semen analysis is highly predictive of male infertility. We conducted a systematic review of published studies that reported pre-orchiectomy semen parameters (as a surrogate for fertility) in TGCT patients to evaluate the association between TGCT and semen abnormalities before orchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…Poor semen quality with reduced fertilization rates is well reported in testicular cancer patients (Hallak et al ., ; Gandini et al ., ; Ping et al ., ; Auger et al ., ). Sperm motility in these patients is reduced and below the WHO reference values of >40% (Djaladat et al ., ; Záková et al ., ; MacKenna et al ., ; Hamano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Poor semen quality with reduced fertilization rates is well reported in testicular cancer patients (Hallak et al ., ; Gandini et al ., ; Ping et al ., ; Auger et al ., ). Sperm motility in these patients is reduced and below the WHO reference values of >40% (Djaladat et al ., ; Záková et al ., ; MacKenna et al ., ; Hamano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in agreement with other larger studies, we observed a trend towards poorer seminal values in men with testicular cancer compared to men presenting with lymphoma (Williams et al ., ; Caponecchia et al ., ). Furthermore, men with abnormal seminal parameters in testicular cancer and lymphoma were oligozoospermic (OZ), oligoasthenozoospermic (OAZ), oligoteratozoospermic (OTZ), oligoasthenoteratozoospermic (OATZ), asthenoteratozoospermic (ATZ) and teratozoospermic (TZ) wherein OZ, OAZ, OTZ, OATZ and ATZ were common in both types of cancer as observed by previous studies (Chung et al ., ; Djaladat et al ., ). In this study, semen parameters fell within the normozoospermic category in 37% and 54% men with testicular cancer and lymphoma, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…These authors presented not only epidemiological evidence, but also histopathological findings, that testosterone production is reduced before a TC diagnosis . After the association between TC and sperm quality was established, a number of studies investigated the semen parameters of patients with TC . Table shows the descriptive studies on pretreatment semen parameters in patients with TC .…”
Section: Fertility and Testicular Cancer Riskmentioning
confidence: 99%
“…21 After the association between TC and sperm quality was established, a number of studies investigated the semen parameters of patients with TC. 22 Table 1 shows the descriptive studies on pretreatment semen parameters in patients with TC. [23][24][25][26][27][28][29] The results of most of the studies indicated that patients with TC show a low sperm concentration and a high rate of abnormal sperm morphology.…”
Section: Fertility and Testicular Cancer Riskmentioning
confidence: 99%